2016
DOI: 10.1002/nme.5264
|View full text |Cite
|
Sign up to set email alerts
|

Delamination growth in composite laminates of variable stiffness

Abstract: SUMMARYThe production of new composite laminates with variable stiffness within the surface of plies was enabled by tow-placement machines. Because of the variation of stiffness, these materials are called variable stiffness composite laminates (VSCL). Recently, many attempts were made to investigate their structural behaviour. In this contribution, a first-order shear deformation theory is selected to model the multilayered composite laminates. The adopted theory is enhanced by the extended finite element met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(3 citation statements)
references
References 32 publications
0
3
0
Order By: Relevance
“…Butler et al [27] applied the finite strip method to study the compression after impact (CAI) performance of delaminated VAT composite plates. Yazdani et al [28] utilized XFEM (Extended Finite Element Method) to analyze the delamination propagation of VAT composite laminates. To the best of the authors' knowledge, no research has been reported in which an attempt has been made to investigate the buckling behaviour of VAT composite plates with delaminations.…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…Butler et al [27] applied the finite strip method to study the compression after impact (CAI) performance of delaminated VAT composite plates. Yazdani et al [28] utilized XFEM (Extended Finite Element Method) to analyze the delamination propagation of VAT composite laminates. To the best of the authors' knowledge, no research has been reported in which an attempt has been made to investigate the buckling behaviour of VAT composite plates with delaminations.…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…the geometric equation g − = 0, the constitutive equation W − = 0, the equilibrium of higher order stress resultants (29) and the constraint (33). Thus, it holds…”
Section: Boundary Value Problem Weak Form and Linearizationsmentioning
confidence: 99%
“…26 The extended finite element method (XFEM) is enlarged for delamination problems in other works. [27][28][29][30][31] Delamination initiation analyses are often based on stress criteria. Especially, the interlaminar stresses as driving forces for this type of failure mode must be known.…”
mentioning
confidence: 99%